IMPLEMENTASI PERATURAN BUPATI NOMOR 34 TAHUN 2019 TENTANG STRATEGI PENANGGULANGAN PERKAWINAN USIA ANAK DI KABUPATEN WONOSOBO - Maria Carolina Lili Wijayanti; Yuwanto Yuwanto (Journal of Politic and Government Studies, 2026)
Early marriage continues to be a social problem that often occurs in various regions, including Wonosobo Regency. As a preventive measure, the Wonosobo Regency Government enacted Regent Regulation Number 34 of 2019 concerning Strategies to Combat Child Marriage. This study aims to analyze the implementation of this regulation and identify the driving and inhibiting factors in its execution. This study uses a qualitative method with a descriptive approach. The data sources consist of primary and secondary data. Primary data were obtained through interviews with relevant parties involved in policy implementation, while secondary data were obtained through documentation studies of regulations, reports, and other supporting documents. The research results show that the implementation of Regent Regulation Number 34 of 2019 has been running quite well and the strategies that were formulated have been carried out, such as child-friendly schools, adolescent reproductive health socialization, parental socialization, as well as gender-responsive and child rights budgeting. Based on George C. Edward III’s policy implementation model, the driving factors in the implementation of this policy include aspects of communication through the socialization that has been conducted, the quality of human resources, the attitude of the implementers, and a bureaucratic structure that is already supported by the existence of SOP’s and clear task fragmentation. However, the implementation of this policy has not yet run optimally. The inhibiting factors found include low public participation and concern regarding the issue of child marriage, limited number of staff and budget, as well as inconsistent implementation of SOP’s in the field.